Exploring the relationship between gender and food safety risks in the dairy value chain in Ethiopia. (January 2022) - Garsow, Ariel V.; Biondi, Marie R.; Kowalcyk, Barbara B.; Vipham, Jessie L.; Kovac, Jasna; Amenu, Kebede; Zewdu, Ashagrie; Colverson, Kathleen E.
Abstract: Women play an important but often unrecognized role in the safe production of milk and milk products, particularly in Ethiopia. Dairy products can be contaminated with biological chemical, and physical hazards. This article reviews literature on the microbiological and/or gendered aspects of milk handling in Ethiopia. Thirty-four articles were reviewed, many of which solely focused on either specific animal and/or foodborne hazards in milk processing or the role of gender in the dairy value chain. Contaminated farm environments put women at higher risk of exposure to milk borne, waterborne, and/or animal borne pathogens. Because of their primary role in animal husbandry, health, and milking, women play a crucial part in ensuring the safety of milk and milk products. To reduce foodborne disease and improve overall family health, there is a need to combine food safety research with gender sensitive interventions in Ethiopia. Highlights: Women in Ethiopia are primarily responsible for the caring and keeping of livestock. Contaminated inputs increase women's risk of exposure to animal/milk borne pathogens. Reduced access to resources is a barrier to technology adoption by women. Women play a crucial role in ensuring the safety of milk through good on farm hygiene. Gender sensitive food safety interventions are needed to reduce exposure to pathogens.